Numerical methods for engineers with personal computer applications - Chapra, Steven C.; Canale, Raymond P. (McGrawHill Education, 2015)
Opening each part with sections called "Motivation" "Mathematical Background" and "Orientation", this book . In this book, each part closes with an "Epilogue" containing "Trade-Offs" "Important Relationships and Formulas" and "Advanced Methods and Additional References"